Therapy of obesity by sibutramin: polymorphisms of TPH2 and GNB3 genes and decrease of body weight - Marina O. Galieva; Ekaterina A. Troshina; Nataliya V. Mazurina; Anna P. Volynkina; Andrey V. Artiushin; Anastasia S. Pavlova (Ожирение и метаболизм, 2018)
Aims. To study of the polymorphisms of the TPN2 and GNB3 genes in obese patients and their effect on weight loss in patients on sibutramine therapy. Materials and methods. The research study included 118 patients with exogenous-constitutional obesity who received Reduxin (sibutramine + CMC) at the dose of 10 mg. Term follow-up was 3 months. A genetic study was performed to assess ТРН2 and GNB3 gene polymorphisms. The response to the therapy was evaluated after 3 months by the dynamics of body weight. Results. In the study the G703T polymorphism of the GNB3 gene showed that during 3 months of observation, carriers of the TT genotype had a greater decrease in body weight in comparison with carriers of the allele C – -8 kg (-12; -5) vs. -5 kg (-8; -3), p = 0.018. In carriers of different variants of the genotype of the TPH2 gene (polymorphism C825T), there was no difference in body weight dynamics with sibutramine therapy. There was no correlation between the foresaid polymorphisms of the TPH2 and GNB3 genes with the indices of blood pressure and heart rate. Conclusions. 1. The result of sibutramin therapy may depend on genetic factors: in carriers of the TT-genotype C825T of the GNB3 gene the body weight loss was higher than among the carriers of the C allele. 2. Changes in blood pressure and heart rate did not show any statistically significant relationship with polymorphisms of the TPH2 and GNB3 genes.